Heat-insulating anti-corrosion composite coating for roof of industrial factory building and preparation method of heat-insulating anti-corrosion composite coating
By using composite coatings containing acrylic resin, diatomaceous earth, hollow alumina spheres and nano alumina on the roof of industrial plants, the problem of low reflection efficiency of traditional coatings in high temperature weather is solved, and the high-efficiency insulation and reflection performance is improved.
Patent Information
- Application Number
- CN202411908512.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-29
AI Technical Summary
The roof insulation coating of traditional industrial factory buildings has low reflection efficiency on sunlight in high temperature weather, resulting in heat transfer to the factory building, and the thermal insulation effect cannot be effectively achieved.
A thermal insulation and corrosion-proof composite coating for roofs of industrial plants is used, and its raw materials include acrylic resin as resin base material, diatomaceous earth and hollow alumina spheres as thermal insulation fillers, and polyimide modified nano-alumina and silane coupling agent as low thermal additive fillers. Through a specific mass ratio and preparation process, an efficient thermal insulation barrier is formed.
This coating significantly reduces heat transfer, improves the reflection performance of the house against sunlight, achieves low thermal conductivity and high reflection thermal insulation, and has excellent stability and durability.
Smart Images

Figure BDA0005205117010000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite coating preparation, and in particular to a heat-insulating and anti-corrosion composite coating for industrial plant roofs and a preparation method thereof. Background Art
[0002] Industrial plant roof insulation coating is an important energy-saving measure aimed at reducing heat transfer, maintaining a stable indoor temperature, and thus improving energy efficiency. Traditional coatings mostly use low thermal conductivity to achieve a certain thermal insulation effect, but in actual use, as the balcony is exposed to the sun in hot weather, the traditional insulation coating has a relatively low reflection efficiency for sunlight, so it will still cause the coating to transfer heat into the plant.
[0003] Therefore, there is an urgent need for a thermal insulation and anti-corrosion composite coating for industrial plant roofs. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a heat-insulating and anti-corrosion composite coating for industrial plant roofs and a preparation method thereof.
[0005] According to one aspect of the present invention, a heat-insulating and anti-corrosion composite coating for industrial plant roofs is provided, wherein the raw materials thereof include the following materials: a resin base material, a heat-insulating filler, and a low-thermal-conductivity additive filler; the mass ratio of the resin base material, the heat-insulating filler, and the low-thermal-conductivity additive filler is 2: (0.11-0.13): (0.22-0.26);
[0006] Preferably, calculated by weight, the raw materials used to prepare the low thermal conductivity additive filler include: 10 to 20 parts of a polyimide modifier, 4 to 6 parts of nano-alumina, and 3 to 5 parts of a silane coupling agent.
[0007] Preferably, the mass ratio of the polyimide modifier, nano-alumina and silane coupling agent is 3:(1.6-1.8):(1.6-1.8).
[0008] In the present invention, the provided heat-insulating and anti-corrosion composite coating for industrial plant roofs uses acrylic resin as a resin base material, and introduces a low-thermal-conductivity additive filler. The main raw material of the low-thermal-conductivity additive filler is polyimide-modified nano-alumina. Polyimide-modified nano-alumina can form a tight oxide protective layer, which effectively resists the erosion of environmental factors such as ultraviolet rays and oxidation. At the same time, the addition of nano-alumina can also improve the corrosion resistance of the coating, so that it can maintain stable thermal conductivity and reflection performance under various harsh environments. In addition, the silane coupling agent in the low-thermal-conductivity filler acts as a bridge to connect inorganic matter (nano-alumina) and organic matter (polyimide modifier), which can effectively improve the compatibility and bonding between the two. The silane coupling agent can also form a chemical bond with the surface of the inorganic material, so that the silane molecules are tightly bound to the surface of the inorganic material, thereby protecting the surface of the inorganic material and effectively improving the anti-corrosion performance of the coating.
[0009] Preferably, calculated by weight, the raw materials used to prepare the resin base material include: 110-120 parts of acrylic resin, 0.5-0.7 parts of cellulose, 0.2-0.4 parts of preservatives, and 1-3 parts of curing agents.
[0010] Preferably, calculated by weight, the raw materials used to prepare the thermal insulation filler include: 40 to 50 parts of diatomaceous earth and 30 to 40 parts of hollow alumina spheres.
[0011] Preferably, the particle size of diatomaceous earth is 300-400 mesh.
[0012] Preferably, the particle size of the hollow alumina sphere is 0.21 to 0.25 mm.
[0013] In the present invention, the heat-insulating and anti-corrosion composite coating for industrial plant roofs is added with heat-insulating fillers, the main raw materials of which are diatomaceous earth and hollow alumina balls. Diatomaceous earth itself has a porous structure and can effectively reduce the conduction of heat, and is a natural heat-insulating material. The hollow alumina balls have a lower thermal conductivity due to their internal hollow structure, which further enhances the heat-insulating effect. When the two are combined, they can form an efficient heat-insulating barrier together, significantly reducing the transfer of heat.
[0014] Preferably, the raw materials for preparing the heat-insulating and anti-corrosion composite coating for industrial plant roofs also include additives, and the mass ratio of the additives to the resin base material is (0.21-0.23):1.
[0015] Preferably, calculated by weight, the raw materials used to prepare the additive include: 6 to 8 parts of thickener, 3 to 7 parts of film-forming aid, 3 to 7 parts of high molecular polymer, 5 to 9 parts of plasticizer, and 7 to 9 parts of titanium dioxide.
[0016] According to another aspect of the present invention, there is provided a method for preparing a heat-insulating and anti-corrosion composite coating for an industrial plant roof, comprising the following steps:
[0017] S1. preparing a resin base at 20 to 25°C, the resin base comprising an acrylic resin, cellulose, a preservative and a curing agent;
[0018] S2. preparing an additive in a stirrer, the additive comprising a thickener, a film-forming agent, a polymer, a plasticizer and titanium dioxide;
[0019] S3. The resin base material and the additive are mixed and stirred at 22 to 25 ° C for 3 to 4 hours, allowed to stand for 24 to 36 hours, and then stirred for a second time at room temperature for 10 to 12 hours to obtain a mixture A;
[0020] S4. Preparing a thermal insulation filler, the thermal insulation filler containing diatomaceous earth and alumina hollow spheres;
[0021] S5. preparing a low thermal conductivity filler, wherein the low thermal conductivity filler contains a polyimide modifier, nano-alumina, and a silane coupling agent;
[0022] S6. Mix the mixture A, the thermal insulation filler, and the low thermal conductivity added filler to obtain a thermal insulation and anti-corrosion composite coating for industrial plant roofs.
[0023] Preferably, after the preparation of the resin base material in step S1 is completed, the pH of the resin base material is adjusted to 7-9.
[0024] Preferably, the stirring speed of step S2 is 1000-1200 rpm, and the stirring time is 2-3 h.
[0025] Preferably, the stirring speed of step S3 is 1200-1500 rpm.
[0026] Preferably, the secondary stirring speed of step S3 is 200-300 rpm.
[0027] In the present invention, the provided heat-insulating and anti-corrosion composite coating for industrial plant roofs uses acrylic resin as the resin base material, and introduces low thermal conductivity additive fillers and thermal insulation fillers. The coating has excellent stability and durability, and has superior thermal insulation and reflection properties, and can achieve the effects of low thermal conductivity and high reflection. DETAILED DESCRIPTION
[0028] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] A heat-insulating and anti-corrosion composite coating for industrial plant roofs is prepared by the following steps:
[0031] S1. A resin base was prepared at 20 ° C, the resin base containing 110 parts by weight of an acrylic resin, 0.5 parts by weight of cellulose, 0.2 parts by weight of a preservative and 1 part by weight of a curing agent;
[0032] S2. An additive is prepared in a stirrer, wherein the additive contains 6 parts by weight of a thickener, 3 parts by weight of a film-forming agent, 3 parts by weight of a polymer, 5 parts by weight of a plasticizer and 7 parts by weight of titanium dioxide;
[0033] S3. The resin base material and the additive were mixed and stirred at 22 ° C for 3 h, allowed to stand for 24 h, and then stirred for a second time at room temperature for 10 h to obtain a mixture A;
[0034] S4. Preparing an insulating filler, the insulating filler containing 40 parts by weight of diatomaceous earth, 30 parts by weight of hollow alumina spheres;
[0035] S5. Preparation of low thermal conductivity filler, low thermal conductivity filler containing 10 parts by weight of a polyimide modifier, 4 parts by weight of nano-alumina and 3 parts by weight of a silane coupling agent;
[0036] S6. Mix mixture A, thermal insulation filler, and low thermal conductivity additive filler to obtain a thermal insulation and anti-corrosion composite coating for industrial plant roofs.
[0037] Among them, the mass ratio of resin base material, thermal insulation filler and low thermal conductivity added filler is 2:0.11:0.22;
[0038] Among them, the mass ratio of polyimide modifier, nano-alumina and silane coupling agent is 3:1.6:1.6;
[0039] Among them, the particle size of diatomaceous earth is 300 mesh;
[0040] Among them, the particle size of the alumina hollow sphere is 0.21 mm;
[0041] Wherein, the mass ratio of the additive to the resin base material in step S3 is 0.21:1.
[0042] Example 2
[0043] A heat-insulating and anti-corrosion composite coating for industrial plant roofs is prepared by the following steps:
[0044] S1. A resin base was prepared at 22 ° C, the resin base containing 115 parts by weight of an acrylic resin, 0.6 parts by weight of cellulose, 0.3 parts by weight of a preservative and 2 parts by weight of a curing agent;
[0045] S2. An additive is prepared in a stirrer, wherein the additive contains 7 parts by weight of a thickener, 5 parts by weight of a film-forming agent, 5 parts by weight of a polymer, 7 parts by weight of a plasticizer and 8 parts by weight of titanium dioxide;
[0046] S3. The resin base material and the additive were mixed and stirred at 23 ° C for 3.5 h, allowed to stand for 30 h, and then stirred for a second time at room temperature for 11 h to obtain a mixture A;
[0047] S4. Preparing an insulating filler, the insulating filler containing 45 parts by weight of diatomaceous earth, 35 parts by weight of hollow alumina spheres;
[0048] S5. Preparation of low thermal conductivity filler, low thermal conductivity filler containing 15 parts by weight of a polyimide modifier, 5 parts by weight of nano-alumina and 4 parts by weight of a silane coupling agent;
[0049] S6. Mix mixture A, thermal insulation filler, and low thermal conductivity additive filler to obtain a thermal insulation and anti-corrosion composite coating for industrial plant roofs.
[0050] Among them, the mass ratio of resin base material, thermal insulation filler and low thermal conductivity added filler is 2:0.12:0.24;
[0051] Among them, the mass ratio of polyimide modifier, nano-alumina and silane coupling agent is 3:1.7:1.7;
[0052] Among them, the particle size of diatomaceous earth is 350 mesh;
[0053] Among them, the particle size of the alumina hollow sphere is 0.23 mm;
[0054] Wherein, the mass ratio of the additive to the resin base material in step S3 is 0.22:1.
[0055] Example 3
[0056] A heat-insulating and anti-corrosion composite coating for industrial plant roofs is prepared by the following steps:
[0057] S1. A resin base was prepared at 22 ° C, the resin base containing 120 parts by weight of an acrylic resin, 0.7 parts by weight of cellulose, 0.4 parts by weight of a preservative and 3 parts by weight of a curing agent;
[0058] S2. preparing an additive in a stirrer, the additive comprising 8 parts by weight of a thickener, 7 parts by weight of a film-forming agent, 7 parts by weight of a polymer, 9 parts by weight of a plasticizer and 9 parts by weight of titanium dioxide;
[0059] S3. The resin base material and the additive were mixed and stirred at 25 ° C for 4 hours, allowed to stand for 36 hours, and then stirred for a second time at room temperature for 12 hours to obtain a mixture A;
[0060] S4. Preparing an insulating filler, the insulating filler containing 50 parts by weight of diatomaceous earth, 40 parts by weight of hollow alumina spheres;
[0061] S5. Preparation of low thermal conductivity filler, low thermal conductivity filler containing 20 parts by weight of a polyimide modifier, 6 parts by weight of nano-alumina and 5 parts by weight of a silane coupling agent;
[0062] S6. Mix mixture A, thermal insulation filler, and low thermal conductivity additive filler to obtain a thermal insulation and anti-corrosion composite coating for industrial plant roofs.
[0063] Among them, the mass ratio of resin base material, thermal insulation filler and low thermal conductivity added filler is 2:0.13:0.26;
[0064] Among them, the mass ratio of polyimide modifier, nano-alumina and silane coupling agent is 3:1.8:1.8;
[0065] Among them, the particle size of diatomaceous earth is 400 mesh;
[0066] Among them, the particle size of the alumina hollow sphere is 0.25 mm;
[0067] Wherein, in step S3, the mass ratio of the additive to the resin base material is 0.23:1.
[0068] Example 4
[0069] This embodiment provides a heat-insulating and anti-corrosion composite coating for industrial plant roofs. Compared with Example 1, the difference in composition is that the low thermal conductivity additive filler is prepared only from nano-alumina. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0070] Example 5
[0071] This embodiment provides a heat-insulating and anti-corrosion composite coating for industrial plant roofs. Compared with Example 1, the difference in composition is that the heat-insulating filler is prepared only from hollow alumina spheres. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0072] Comparative Example 1
[0073] Comparative Example 1 is a heat-insulating and anti-corrosion composite coating commonly used on the market for industrial plant roofs.
[0074] Test Case
[0075] 1. Test subjects
[0076] In this test example, the heat-insulating and anti-corrosion composite coatings for industrial plant roofs prepared in Examples 1 to 5 and the heat-insulating and anti-corrosion composite coatings for industrial plant roofs commonly available on the market in Comparative Example 1 were used as test objects to conduct relevant performance tests.
[0077] 2. Test content
[0078] (1) pH value
[0079] (2) Viscosity
[0080] (3) Thermal conductivity
[0081] 3. Test results
[0082] Table 1 Related performance tests of heat insulation and anti-corrosion composite coatings for industrial plant roofs
[0083]
[0084] The relevant performance test results of the heat-insulating and anti-corrosion composite coatings for industrial plant roofs provided in Examples 1 to 5 and Comparative Example 1 are shown in Table 1.
[0085] The pH values of all examples are between 7.5 and 8.3, indicating that these coatings are neutral or slightly alkaline, suitable for roof applications in most industrial plants, and will not corrode roofing materials. The pH value of Comparative Example 1 is 7.3, which is also close to neutral, but slightly lower than that of other examples. The difference in pH values may be due to the formulation and preparation process of different coatings.
[0086] The viscosity values of all examples are very close, ranging from 94.9 to 95.4 seconds, indicating that the fluidity of these coatings is similar and easy to apply. The viscosity value of Comparative Example 1 is slightly lower (94.8 seconds), but the difference is not large, indicating that the viscosity of the examples is similar to that of the products on the market.
[0087] The thermal conductivity of Examples 1 to 3 gradually increased, but remained at a low level (0.11 to 0.13 W / (m·k)), indicating that these coatings have good thermal insulation properties. The increase in thermal conductivity may be related to the content or type of thermal insulation fillers and low thermal conductivity added fillers in the coating. The thermal conductivity of Examples 4 and 5 increased significantly (0.21 to 0.22 W / (m·k)), which may be because the formulation of the thermal insulation filler or low thermal conductivity added filler in these two examples has changed. Specifically, Example 4 removes the polyimide modifier and the silane coupling agent, and only uses nano-alumina as a low thermal conductivity added filler; Example 5 removes diatomaceous earth and only uses hollow alumina balls as thermal insulation fillers. These changes may reduce the thermal insulation properties of the coating. The thermal conductivity of Comparative Example 1 is lower than 0.045 W / (m·k), indicating that its thermal insulation performance is better than all the examples. This may be because Comparative Example 1 uses a more advanced thermal insulation material or preparation process.
[0088] In summary, the thermal insulation and anti-corrosion composite coatings for industrial plant roofs of Examples 1 to 3 all show good performance in terms of pH value, viscosity and thermal conductivity. However, compared with the products on the market, the thermal conductivity of the examples is slightly higher, and further optimization of the formula and preparation process may be required to improve the thermal insulation performance. At the same time, the results of Examples 4 and 5 show that the type and content of thermal insulation fillers and low thermal conductivity added fillers have a significant effect on the thermal insulation performance of the coating.
[0089] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A heat-insulating and anti-corrosion composite coating for industrial plant roofs, characterized in that: Its raw materials include the following materials: resin base material, thermal insulation filler, low thermal conductivity added filler; The mass ratio of the resin base material, the thermal insulation filler and the low thermal conductivity additional filler is 2: (0.11~0.13):(0.22~0.26)。 2. The heat-insulating and anti-corrosion composite coating for industrial plant roofs according to claim 1, characterized in that: Calculated by weight, the raw materials used to prepare the low thermal conductivity additive filler include: 10 to 20 parts of polyimide modifier, 4 to 6 parts of nano-alumina, and 3 to 5 parts of silane coupling agent.
3. The heat-insulating and anti-corrosion composite coating for industrial plant roofs according to claim 2, characterized in that: The mass ratio of the polyimide modifier, the nano-alumina and the silane coupling agent is 3:(1.6-1.8):(1.6-1.8).
4. The heat-insulating and anti-corrosion composite coating for industrial plant roofs according to claim 1, characterized in that: Calculated by weight, the raw materials used to prepare the resin base material include: 110-120 parts of acrylic resin, 0.5-0.7 parts of cellulose, 0.2-0.4 parts of preservatives, and 1-3 parts of curing agents.
5. The heat-insulating and anti-corrosion composite coating for industrial plant roofs according to claim 1, characterized in that: Calculated by weight, the raw materials used to prepare the thermal insulation filler include: 40 to 50 parts of diatomaceous earth and 30 to 40 parts of hollow alumina balls.
6. The heat-insulating and anti-corrosion composite coating for industrial plant roofs according to claim 1, characterized in that: The raw materials also include additives, and the mass ratio of the additives to the resin base material is (0.21-0.23):
1.
7. The heat-insulating and anti-corrosion composite coating for industrial plant roofs according to claim 6, characterized in that: Calculated by weight, the raw materials used to prepare the additive include: 6 to 8 parts of thickener, 3 to 7 parts of film-forming aid, 3 to 7 parts of high molecular polymer, 5 to 9 parts of plasticizer, and 7 to 9 parts of titanium dioxide.
8. A method for preparing a heat-insulating and anti-corrosion composite coating for industrial plant roofs as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: S1. preparing a resin base at 20 to 25°C, wherein the resin base comprises the acrylic resin, the cellulose, the preservative and the curing agent; S2. preparing an additive in a stirrer, wherein the additive contains the thickener, the film-forming agent, the polymer, the plasticizer and the titanium dioxide; S3. The resin base material and the additive are mixed and stirred at 22 to 25 ° C for 3 to 4 hours, allowed to stand for 24 to 36 hours, and then stirred for a second time at room temperature for 10 to 12 hours to obtain a mixture A; S4. Preparing a thermal insulation filler, wherein the thermal insulation filler contains the diatomaceous earth and the hollow alumina spheres; S5. preparing a low thermal conductivity filler, wherein the low thermal conductivity filler contains the polyimide modifier, the nano-alumina, and the silane coupling agent; S6. Mix the mixture A, the thermal insulation filler, and the low thermal conductivity added filler to obtain a thermal insulation and anti-corrosion composite coating for industrial plant roofs.
Citation Information
Patent Citations
Nanometer heat isolation paint and preparation method thereof
CN102504661A
Waterborne acrylate waterproof heat-insulation building coating and preparation method thereof
CN107556854A
Preparation method of nano thermal insulation energy-saving coating
CN110396337A
Water-resistant heat-resistant thermosensitive anti-forgery ink and preparation method thereof
CN118725637A